GinkgoDB: an ecological genome database for the living fossil, Ginkgo biloba. (27th June 2022) - Gu, Kai-Jie; Lin, Chen-Feng; Wu, Jun-Jie; Zhao, Yun-Peng
Abstract: Although an increasing number of species-specific databases have been constructed to facilitate the global research community, comprehensive databases remain rare with multidimensional research resources rather than genomic data solely, in particular for non-model species. Here we introduced GinkgoDB, the ecological genome database for the world-renowned living fossil, Ginkgo biloba L., a tree species with extreme longevity, exceptional resistance, global landscape application and dioecy. The present version of GinkgoDB consists of four modules of genome, occurrence, quadrat and gallery. The genome module includes two versions of chromosome-level assembled genomes with high-quality annotation, expression profiles of each sex for different tissues and variants from 545 ginkgo genomes. A suite of tools were also deployed online for search, blast and further analyses. The occurrence module contains distribution information of over one million records across the world with an emphasis on 8926 individual-level tagged trees with phenotypic trait data in eastern Asia. The quadrat module provides monitoring data of both species and habitats from 27 plots of natural ginkgo forests and periodic data of functional traits measured for the entire plant communities. The gallery module collects field morphological photos and scanned phenotypic images of various ginkgo materials. GinkgoDB showcases a comprehensive and persistently growing database for a single non-model species. Database URL : https://ginkgo.zju.edu.cn/